Enhancing glioblastoma treatment through the integration of tumor-treating fields - Szklener, Katarzyna; Bilski, Mateusz; Nieoczym, Karolina; Mańdziuk, Dominika; Mańdziuk, Sławomir (Frontiers in Oncology, 2023)
Glioblastoma (GBM) represents a significant therapeutic challenge due to its aggressive nature. Tumor Treating Fields (TTFields) present a promising approach to GBM therapy. The primary mechanism of TTFields, an antimitotic effect, alongside numerous indirect effects including increased cell membrane permeability, signifies their potential in combination with other treatment modalities. Current combinations often include chemotherapy, particularly with temozolomide (TMZ), however, emerging data suggests potential synergy with targeted therapies, radiotherapy, and immunotherapy as well. TTFields display minimal side effects, predominantly skin-related, posing no significant barrier to combined therapies. The effectiveness of TTFields in GBM treatment has been demonstrated through several post-registration studies, advocating for continued research to optimize overall survival (OS) and progression-free survival (PFS) in patients, as opposed to focusing solely on quality of life.